AN EDUCATIONAL GAME APPLICATION TO ASSIST THE COMMUNITY IN REMEMBERING ROAD DIRECTIONS AND PLACES IN PALEMBANG - Nadya Angelia; Miftahul Jannah; Albert Amadeus Valentino; Michelle Liu; Ali Ibrahim (Jurnal Riset Informatika, 2021)
Visuospatial processing is one of the important aspects of everyday life, whether it is to travel or to recognize the location of objects around. Visuospatial processing can be improved in various way, one of which is by using repetition. WorldVenture app was created to help its users improve their visuospatial capability by remembering landmarks in the city where they live. WorldVenture was created using flutter framework with five steps, namely literature study, data and information collection, application designing, testing, and evaluation. This app will have three main features: Flashcard, Quiz, and Notes. WorldVenture testing result, using questionnaires, showed 64,5% people out of 30 respondents rated WorldVenture excellent for improving visuospatial capabilities and as many as 35.5% of respondents rated it good.